Cryptocurrencies as a means of payment in online shopping - Al Reshaid, Faisal (2024)
Purpose: Cryptocurrencies are becoming increasingly attractive as alternatives to traditional currencies. Although many retailers accept cryptocurrencies as a means of payment in online shopping, consumers’ cryptocurrency adoption intention in online shopping (CCAI) is still low. This study aims to investigate the influence of attitudes, subjective norms, consumer trust, financial literacy and fear of missing out (FOMO) on CCAI. Design/methodology/approach: A quantitative research approach was followed using a consumer survey. Hypothesized relationships were tested through regression and mediation analyses. Findings: The results revealed that consumers could accept cryptocurrencies as a means of payment in online shopping. Attitudes, subjective norms, consumer trust and financial literacy directly and positively influence CCAI, while they indirectly affect CCAI through the mediating impact of FOMO. Practical implications: Marketing managers should improve consumers’ knowledge about cryptocurrencies and trust in online shopping to increase CCAI. Social media marketing can be appropriate, while the advertising content can address keeping up with others and staying connected. Originality/value: This study addresses a critical gap in the literature by empirically examining the antecedents of CCAI within an original conceptual model based on the theoretical framework provided by the theory of planned behavior. Attitudes, subjective norms, trust and financial literacy influence CCAI, where FOMO plays a significant role as a mediator.